Effect of an Intensive Mindful Practice Workshop on Patient-Centered Compassionate Care, Clinician Well-Being, Work Engagement, and Teamwork. Issue 1 (27th August 2022) - Epstein, Ronald M.; Marshall, Frederick; Sanders, Mechelle; Krasner, Michael S.
Abstract : Introduction: Mindfulness-based interventions for health professionals have been linked to improvements in burnout, well-being, empathy, communication, patient-centered care, and patient safety, but the optimal formats and intensity of training have been difficult to determine because of the paucity of studies and the heterogeneity of programs. A 4-days residential "Mindful Practice" workshop for physicians and medical educators featuring contemplative practices, personal narratives, and appreciative dialogs about challenging experiences may hold promise in improving participants' well-being while also improving compassionate care, job satisfaction, work engagement, and teamwork. Methods: We collected baseline and 2-month follow-up data during four workshops conducted in 2018 to 2019 at conference centers in the United States and Europe. Primary outcomes were burnout, work-related distress, job satisfaction, work engagement, patient-centered compassionate care, and teamwork. Results: Eighty-five of 120 participants (71%) completed both surveys (mean age was 49.3 and 68.2% female). There were improvements ( P < .01) in two of three burnout components (emotional exhaustion and depersonalization), work-related distress, job satisfaction, patient-centered compassionate care, work engagement and meaning, teamwork, well-being, positive emotion, mindfulness, somatic symptoms, and spirituality. Effect sizes (standardized mean difference of change) ranged from 0.25 to 0.61. With Bonferroni adjustments ( P < .0031), teamwork, general well-being, and mindfulness became nonsignificant. Discussion: An intensive, multiday, mindfulness-based workshop for physicians had clinically significant positive effects on clinician well-being, quality of interpersonal care and work satisfaction, and meaning and engagement, all important indicators of improved health and sustainability of the health care workforce. Future iterations of the program should increase the focus on teamwork.